Dampak Kalkulasi Biaya Variabel terhadap Pengambilan Keputusan Manajerial: Systematic Literature Review dengan Metode Prisma - Dhea Pramestie Aryani; Nabila Khairunnisa Ahmad; Maria Bianca Cheravin; Afifah Alya Zulaikha; Novi Karsa Pratiwi; Rifani Akbar Sulbahri (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Accurate cost information plays an essential role in supporting managerial decision-making in modern business environments. In many organizations, however, the selection of appropriate costing methods remains a challenge, particularly when managers need reliable cost data to evaluate operational performance and determine strategic actions. This study aims to review and synthesize existing research on the role of variable costing in managerial decision-making across different industrial contexts. The study employs a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 framework to ensure a transparent and structured literature selection process. Relevant publications were collected from the Scopus and Google Scholar databases within the period 2016-2026 using keywords related to variable costing and managerial decision-making. After applying several screening and eligibility criteria, 16 studies were selected for further analysis. The review shows that variable costing provides more relevant cost information for short-term managerial decisions compared to traditional full costing approaches. Prior studies consistently report that the method supports pricing decisions, profit planning, cost control, and evaluation of special orders. Overall, the findings highlight the continued relevance of variable costing as an important tool in managerial accounting for improving the quality of managerial decisions in various sectors.